2020
DOI: 10.1021/acs.est.0c03691
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget Screening and Toxicity Evaluation of Diol Esters of Okadaic Acid and Dinophysistoxins Reveal Intraspecies Difference of Prorocentrum lima

Abstract: High-resolution mass spectrometry (HRMS) analysis with the assistance of molecular networking was used to investigate intracellular toxin profiles of five Prorocentrum lima (P. lima) strains sampled from the north Yellow Sea and South China Sea. Mice were used as a model species for testing the acute toxicity of intracellular okadaic acid (OA) and dinophysistoxins (DTXs) in free and esterified states. Results showed that OA and DTX1 esterified derivatives were detected in all P. lima samples, accounting for 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…The origins of the OA & DTXs & PTXs group in marine species have been identified as the dinoflagellates of Dinophysis and Prorocentrum spp. , In addition, the OA & DTXs & PTXs group profiles produced by P. lima can be classified into two types based on the ratio of OA/DTXs (ratio > 1 and ratio ≤ 1), and the ratios of free OA/DTX1 in several strains of P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origins of the OA & DTXs & PTXs group in marine species have been identified as the dinoflagellates of Dinophysis and Prorocentrum spp. , In addition, the OA & DTXs & PTXs group profiles produced by P. lima can be classified into two types based on the ratio of OA/DTXs (ratio > 1 and ratio ≤ 1), and the ratios of free OA/DTX1 in several strains of P.…”
Section: Resultsmentioning
confidence: 99%
“…62 The origins of the OA & DTXs & PTXs group in marine species have been identified as the dinoflagellates of Dinophysis and Prorocentrum spp. 52,63−65 In addition, the OA & DTXs & PTXs group profiles produced by P. lima can be classified into two types based on the ratio of OA/DTXs (ratio > 1 and ratio ≤ 1), and the ratios of free OA/DTX1 in several strains of P. lima found in the SCS were generally below 1, 63 whereas the ratios of free OA/DTX1 in our studied mollusks (5 out of 7 species, 71.4%), crustaceans (5 out of 5 species, 100%), and fishes (5 out of 5 species, 100%) were commonly higher than 1; the proportion of the OA & DTXs & PTXs group in the total MLPs in fishes (mean, 74%) was higher than that in the benthos (mean, 29% for mollusks and 40% for crustaceans), which can be explained by differences in the uptake-depuration of OA and DTXs among the three taxonomic groups. For example, a comparable net accumulation efficiency between OA and DTX1b was reported in blue mussels (Mytilus edulis) fed toxigenic D. acuta.…”
Section: Resultsmentioning
confidence: 99%
“…The Global Natural Products Social Molecular Networking Platform (GNPS) is based on spectral alignment to assess the similarities and relationships among molecules (Wang et al, 2016) and visualized using a molecular network. While GNPS is mainly used for biodiscovery of natural products (Teta et al, 2015;Naman et al, 2017;Ding et al, 2018;Via et al, 2018), it has been recently applied to dinoflagellate metabolites and demonstrated the unique metabolites from these organisms (Fiorini et al, 2020;Wu et al, 2020;Sibat et al, 2021). Molecular networking of five Dinophysis species identified the characteristic toxin profile for each strain and identified five new putative pectenotoxins (Sibat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with unprecedented chemical scaffolds in Pseudo-nitzchia extracts, not represented in reference databases, were observed (Fiorini et al, 2020). Improved qualitative and quantitative screening of okadaic acid and dinophysistoxins was achieved through molecular networking of extracts from Prorocentrum lima (Wu et al, 2020). New esters of okadaic acid and dinophysistoxins were also identified (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation